Flowing ability of self-consolidating concrete and its binder paste and mortar components incorporating rice husk ash - Safiuddin, M.; West, J.S.; Soudki, K.A. (National Research Council Canada, 2010)
This paper presents the flowing abilities of various self-consolidating concretes (SCCs) and their binder paste and mortar components. The binder pastes and mortars were formulated from the concrete mixtures and tested for flowing ability with respect to flow time and flow spread, respectively, at various dosages of high-range water reducing admixture (HRWRA). The concrete mixtures were prepared with different water (W) to binder (B) ratios and rice husk ash (RHA) contents. The flowing ability of the concretes was measured with regard to slump flow, orimet flow time and flow spread, and inverted slump cone flow time and flow spread. The test results reveal that the W:B ratio, RHA content, and HRWRA dosage significantly influenced the flowing abilities of the binder pastes, mortars, and concretes. In addition, the flowing ability of the SCCs was well correlated with the flowing abilities of their binder paste and mortar components, except for the mortars including RHA.